2012
DOI: 10.1111/j.1365-4632.2011.05016.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin infections and infestations in prison inmates

Abstract: Skin infections and infestations are common in prison. A change in living conditions and personal hygiene will definitely help in reducing these infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 5 publications
(6 reference statements)
6
25
0
2
Order By: Relevance
“…Our data are similar to those of Oninla OA et al, [8] in Nigeria, which found 63.6% infectious dermatosis, 36.4% non-infectious dermatosis. Among infectious dermatosis, 59.1% (146/247) of mange, 39.6% (98/247) of mycotic dermatosis dominated by dermatomycosis were found in 58 patients, i.e., 23.4% followed by pityriasis versicolor in 38 Patients, is 15.3%.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our data are similar to those of Oninla OA et al, [8] in Nigeria, which found 63.6% infectious dermatosis, 36.4% non-infectious dermatosis. Among infectious dermatosis, 59.1% (146/247) of mange, 39.6% (98/247) of mycotic dermatosis dominated by dermatomycosis were found in 58 patients, i.e., 23.4% followed by pityriasis versicolor in 38 Patients, is 15.3%.…”
Section: Discussionsupporting
confidence: 81%
“…Among infectious dermatosis, 59.1% (146/247) of mange, 39.6% (98/247) of mycotic dermatosis dominated by dermatomycosis were found in 58 patients, i.e., 23.4% followed by pityriasis versicolor in 38 Patients, is 15.3%. In our study, as in those of several other doi: 10.7243/2053-5309-5-1 authors, mycotic conditions also remain of high prevalence in prison settings [8,13,14]. In the study by B. Khatibi et al in France, the low rate of scabies was due to the anti-scabious treatment and to the isolation during one week of the prisoners for whom this diagnosis was evoked during the systematic medical consultation that follows their Transfer from their place of custody [12].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…All these infectious dermatoses are favored by several factors such as: poor sanitary conditions, sharing personal effects and poor access to medical and water supplies. In additions, a factor like overcrowding creates a hot humid environment that predispose to such skin infections by skin contact [3]. It is recognized that poverty deprives individuals of the freedom to satisfy basic needs and rights.…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, infectious dermatoses account for up to 85% of skin conditions and 71% of cases in Ethiopia [1,2]. These infectious dermatoses are mostly caused by fungal, parasite agents and sometimes bacterial and viral agents [3]. In Côte d'Ivoire, infectious dermatoses remain frequent issues in primary health care setting, where there are no dermatologists.…”
Section: Introductionmentioning
confidence: 99%